Haemoglobin level fluctuations – do they impact on outcome of CKD patients treated with erythropoietin? - Stompór, Tomasz (Przewodnik Lekarza/Guide for GPs, 2007)
Introduction of recombinant human erythropoetin to the treatment of patients with end-stage renal disease was considered as substantial therapeutic progress. Several benefits, initially considered to be associated with this drug (such as decreased risk of cardiovascular morbidity and mortality, regression of cardiac structure and function abnormalities, improved survival) were not confirmed in the series of controlled, prospective, randomized clinical studies. Most of these trials failed to demonstrate any substantial benefits from achieving higher hemoglobin levels with higher doses of erythropoetin. Several possible explanations for such a lack of improvement have been identified. Recently, attention has been focused on the substantial hemoglobin variability in individual patients, which leads to several Hb values out of the target range, despite of the mean value being well within the range. The question emerged whether the new erythropoesis stimulating agents with prolonged half-life could possibly increase hemoglobin stability over time and whether such an increased stability will translate into improved patients’ outcome.